Pasca-Islamisme dalam PAS: analisis terhadap kesan tahalluf siyasi - Muhammad Faiz Mukmin Abdul Mutalib; Wan Fariza Alyati Wan Zakaria (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
This study discusses the impact of post-Islamism in the Parti Islam Se-Malaysia (PAS), specifically on tahalluf siyasi (political alliance) with Pakatan Rakyat (People Coalition). Post Islamism is a contemporary Islamist school of thought with regard to politics. The characteristics of post-Islamism such as toleration, participation and inclusivism has greatly influenced the modus operandi of the Islamic movement including PAS. Inclusiveness in post-Islamism had motivated PAS in having political coalition with more liberal parties such as Parti Keadilan Rakyat (PKR) and Democratic Action Party (DAP). Post-Islamism as popularised by Asef Bayat was established on Western knowledge narratives, therefore such study as this should be done in order to recognise its negative impacts. To achieve this objective, the researchers used qualitative method through the process of collecting by scrutinising and analysing related data on the discourse of post-Islamism. The result of the study shows that PAS has been affected by the post-Islamism. The impact of post-Islamism in PAS however shows that PAS did not play dominant role in the Coalition throughout the political alliance. Besides, PAS also compromised a lot with its principles including its Islamic principles. Post-Islamism had also affected PAS in reducing the Muslims vote to PAS because of their support for DAP. This study therefore exposed the negative sides of post-Islamism to Islamic movement. With current development in PAS, it is hoped that this exposure will consult the Islamic movements in critically weighing their support to any kind of ideas particularly from the West.